Enhanced electromagnetic wave absorption properties of planar anisotropy carbonyl-iron/Fe3O4 composites in gigahertz range. (May 2014) - Zou, J.; Liu, Q.; Zi, Z.; Dai, J.
<x content-type="archive" xml:space="preserve">Abstract</x> The planar anisotropy ball milling carbonyl-iron/Fe3O4 composites (BMCI/Fe3O4) have been synthesised via ball milling technique and hydrothermal method. The constituents, phase, and morphology have been characterised by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The electromagnetic wave absorption properties are measured by vector network analysis (VNA). The results indicate that BMCI/Fe3O4 composites synthesised in the pH values of 12 and 13 have absorption peak values of about −33·5 dB at 3·9 GHz and −28·2 dB at 4·2 GHz respectively, when the volume fraction of BMCI/Fe3O4 composites is only 20% and the matching thickness is 3·0 mm. A layer of ferromagnetic Fe3O4 crystals on the surface of BMCI has an obvious effect on the electromagnetic wave absorption properties of composites. A possible mechanism of the improved electromagnetic wave absorption properties of the composite has also been discussed.